Inherited determinants of early recurrent somatic mutations in prostate cancer - Alessandro Romanel (Nature Portfolio, 2017)
Prostate cancer is a heterogeneous disease, and many cases show somatic mutations of SPOP. Here, the authors show that a non-coding polymorphic regulatory element at 7p14.3 may predispose to SPOP mutant prostate cancer subclass through a hormone dependent DNA damage response.